Ethanol Induces Enhanced Vascularization Bioactivity of Endothelial Cell-Derived Extracellular Vesicles via Regulation of MicroRNAs and Long Non-Coding RNAs - Tek N. Lamichhane (Nature Portfolio, 2017)
Abstract Extracellular vesicles (EVs), such as exosomes, have been identified as regulators of vascular remodeling and have promise as therapeutics for vascularization applications. Towards development of EVs as therapeutics, it has been demonstrated that physiological stimuli of angiogenic phenotypes in EV-producing cells can enhance the potency of EVs for vascularization. The goal of this study was to assess whether ethanol, which induces angiogenic phenotypes in endothelial cells, could be employed to enhance endothelial-derived EV vascularization bioactivity. The results indicate that ethanol conditioning of endothelial cells increases the ability of endothelial EVs to induce a pro-vascularization response. This response is due in part to increased CD34 expression in recipient endothelial cells that may result from downregulation of microRNA-106b in EVs isolated from ethanol-conditioned producer endothelial cells. Further, ethanol-induced upregulation of long non-coding RNAs (lncRNAs) HOTAIR and MALAT1 in endothelial EVs was observed to play a significant role in mediating pro-angiogenic effects of these vesicles. Overall, these studies validate ethanol conditioning as a method to enhance the bioactivity of endothelial EVs via regulation of EV-associated microRNAs (miRNAs) and, especially, lncRNAs. Further, the results suggest that alcohol consumption may activate endothelial EVs towards a pro-vascularization phenotype, which could have implications for alcohol-induced tumor angiogenesis.